Comparison of effectiveness of metered dose inhaler with spacer and jet nebulizer in children aged 5-14 years with acute exacerbation of asthma: A pilot randomized controlled trial - Kundan Mittal; Rishabh Batra; Alok Khanna (Wolters Kluwer Medknow Publications, 2021)
Background: Asthma is a common and potentially serious chronic disease that imposes a substantial burden on patients, their families, and community. The main treatment of an acute exacerbation includes inhaled short-acting β2-agonists (SABA). The aim of this of study was to compare the effectiveness of metered dose inhaler (MDI) with spacer and jet nebulizer for delivering SABA in children aged 5-14 years presenting to the emergency department with acute asthma. Subjects and Methods: One hundred subjects were randomly assigned to receive salbutamol by an MDI with spacer or a nebulizer at fixed intervals. The parameters such as respiratory rate, heart rate, use of accessory muscles, auscultatory findings, peak expiratory flow rate (PEFR), development of tremor, pCO2 on venous blood gas, need for hospital admission, and duration of stay in the emergency department were compared between two groups. Statistical tests used were Student's t-test, Chi-square test, and Fisher's exact test. Results: Clinical improvement in the form reduction of respiratory rate, use of accessary muscles, wheeze, and PEFR was comparable between two groups. Increase in heart rate in children with MDI with spacer group was significantly lower (P < 0.001) than that of nebulizer group at all time intervals during the study period. No significant difference was observed for the need of pediatric intensive care unit admission, duration of stay in emergency department, and adverse events between two groups. Conclusions: In children aged 5-14 years presenting to the emergency department with acute exacerbation of asthma, the efficacy of MDI with spacer for delivering SABA was comparable with that of nebulizer.